PERANCANGAN SISTEM INFORMASI PENDAFTARAN POLI GIGI MENGGUNAKAN METODE RAD - Arni Hardiyanti; Falaah Abdussalam; Erix Gunawan (LPSDI Bina Patria, 2024)
Abstract Currently, information systems technology is growing rapidly, and its use has penetrated various fields, including the health sector. Hermina Hospital is one of the hospitals that provides services for patients who are going for dental treatment. Because the management of patient reports is still done manually, it is necessary to design an accurate application in order to obtain dental patient reports that can be integrated with fast, precise, effective, and efficient processes. This electronic application is specifically designed for polydental installations. The use of visual basic information technology in medical management has the aim of assisting health workers in collecting data for the hospital reporting process. The research method used is the descriptive-qualitative method, where data collection is in the form of observation, interviews, and literature study and uses a system development method, namely the RAD method. This information system is specifically designed for dental patients, which will make it easier for registration officers, and besides that, it will be very easy for officers to make daily, monthly, or yearly reports using the system that has been created.